Clusters de la industria en el Perú - Torres Zorrilla, Jorge (2003)
This study presents a cluster analysis of all industrial sectors in Peru, which is derivedfrom the information contained in the input-output matrix of the Peruvian economy for the year1994. The study lists the most important firms in every cluster, it describes the production linksamong firms and the final destination of all outputs, and it provides information on who are theowners of some of the most important firms. The conclusions of the study are: (i) industrialclusters in Peru are yet in the first stages of development; (ii) there are limitations for furtherclustering due to: low technological capabilities, to lack of capacity to generate innovations andtransfer learning experiences, to insufficient domestic demands which only allow small scales ofproduction, and to present-day restrictions for external financing and new direct foreigninvestment; (iii) the most-developed industrial clusters in Peru are those related to the exportingcomplexes of the economy: Mining-Metal Industries, Fishing, and Textiles.